Is MRI-Linac helpful in SABR treatments for liver cancer? - Tallet, Agnès; Boher, Jean-Marie; Tyran, Marguerite; Mailleux, Hugues; Piana, Gilles; Benkreira, Mohamed; Fau, Pierre; Salem, Naji; Gonzague, Laurence; Petit, Claire; Darréon, Julien (Frontiers in Oncology, 2023)
Objective: To determine the MRI-Linac added value over conventional image-guided radiation therapy (IGRT) in liver tumors Stereotactic ablative radiation therapy (SABR). Materials and methods: We retrospectively compared the Planning Target Volumes (PTVs), the spared healthy liver parenchyma volumes, the Treatment Planning System (TPS) and machine performances, and the patients' outcomes when using either a conventional accelerator (Versa HD, Elekta, Utrecht, NL) with Cone Beam CT as the IGRT tool or an MR-Linac system (MRIdian, ViewRay, CA). Results: From November 2014 to February 2020, 59 patients received a SABR treatment (41 and 18 patients in the Linac and MR-Linac group, respectively) for 64 primary or secondary liver tumors. The mean tumor size was superior in the MR-Linac group (37,91cc vs. 20.86cc). PTV margins led to a median 74%- and 60% increase in target volume in Linac-based and MRI-Linac-based treatments, respectively. Liver tumor boundaries were visible in 0% and 72% of the cases when using CBCT and MRI as IGRT tools, respectively. The mean prescribed dose was similar in the two patient groups. Local tumor control was 76.6%, whereas 23.4% of patients experienced local progression (24.4% and 21.1% of patients treated on the conventional Linac and the MRIdian system, respectively). SABR was well-tolerated in both groups, and the use of MR-guided radiation therapy prevented ulcerous disease occurrence. Conclusion: The use of MRI as IGRT allows for the reduction of the amount of healthy liver parenchyma irradiated without any decrease of the tumor control rate, which would be helpful for dose escalation or subsequent liver tumor irradiation if needed. On-line adaptive treatments seem to reduce gastrointestinal toxicity.